Characterization of Fluorescent Rhizobacteria Isolated From Oleander (Nerium oleander L.) and Olivier (Olea oleaster L.) With Antagonistic Effect Against Fusarium oxysporum f. sp. radicis-lycopersici - Hadj Ahmed BELAOUNI; Mohammed El-Amine BENDAHA; Bouziane ABBOUNI; Mostefa NAIMI; Mohamed LABDI (Revue Nature et Technologie, 2022)
This study aims to characterize the biocontrol potential of two fluorescent rhizobacteria isolated from Oleander (Nerium oleander L.) and Olivier (Olea oleaster L.). The isolation was done in Cetrimide agar. The fluorescing strains at 366 nm were selected for the dual plate assay against the tomato pathogen Fusarium oxysporum f.sp. radicis-lycopersici. The two best strains showing the highest inhibition rates (Pa2 and S2Pf1 with 31.36% and 51.42% respectively) were chosen to be identified and characterized for their production of antifungal molecules. The taxonomical determination based on macro and micromorphological observations in addition to the biochemical tests of the API 20E and API 20NE strips analyzed by the heuristic soft "PIBwin 2.0.0" suggests the strain Pa2 as a Pseudomonas aeruginosa while the strain S2Pf1 belongs to the Burkholderia cepacia species. The antifungal potential was assessed through the quantification/detection of the following bioactive molecules: salicylic acid, hydrogen cyanide, rhamnolipids, chitinases, and cellulases. The strain Burkholderia cepacia S2Pf1 showed a better antifungal profile in comparison to Pseudomonas aeruginosa Pa2. The determination of the growth kinetics parameters of Burkholderia cepacia S2Pf1 based on observed OD600 data, DModel data fitting, and Gompertz model data fitting highlighted a relatively good ability to quickly reach high bacterial densities in both nutrient and seed broths. Thus, Burkoledria cepacia S2Pf1 is suggested as a good candidate to be further assessed for its biocontrol proprieties against Fusarium oxysporum f.sp. radicis-lycopersici.